Pengaruh Profitabilitas dan Likuiditas terhadap Nilai Perusahaan pada Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Dio Saputra; Rani Kurniasari; Teni Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
Transportation and logistics companies are one among the elements influencing Indonesia's economic growth. In recent years, many companies in this sector have ceased operations because there aren't enough users and the emergence of similar competitors. The financial results of this have been affected by each company and affected their growth. In this thesis, the The researcher's objective is.to investigate how.profitability and liquidity.impact the.value of transportation and logistics firms during the years 2021–2024. Return on assets (ROA) is used to determine profitability, and to ascertain liquidity, the current ratio (CR) is utilized. The annual reports of businesses that are listed on the stock exchange provided the financial data used in this investigation. The multiple regression analysis was used to evaluate the hypotheses. The findings of this investigation show thatt, the firm value variable is significantly and favorably impacted by both the profitability and liquidity factors. The significance value (Sig) of the profitability variable is 0.000 < 0.05, and the calculated t-value is 6.064 > 1.668. The significance level (Sig) of the Liquidity variable is 0.006 < 0.05, and the calculated t-value is 2.813 > 1.668. The results of this study indicate that, individually, each variable has a positive and significant effect on company value for transportation and logistics companies during the 2021-2024 period. The simultaneous results of the study on the efficiency and liquidity metrics on the variable of Company Value have a Sig value of 0.000 < 0.05 and a calculated F value of 29.266 > 3.14. Therefore, the study's findings show that company value.is impacted by both profitability and liquidity.at the same time.